PENGARUH KUALITAS PRODUK DAN PROMOSI TERHADAP KEPUTUSAN PEMBELIAN PELANGGAN PRODUK PT. SAYAP MAS UTAMA - Clara Putri Claudy; Donny Dharmawan (Program Studi Magister Manajemen Universitas Krisnadwipayana, 2021)
To describe product quality, promotion and customer purchasing decision products of PT. Sayap Mas Utama, and to analysis the effect of quality products on customer ourchasing decisions PT. Sayap Mas Utama. This study uses data collection methods. Using a questionnaire, the data analysis method used is descriptive analysis, simple liner regression. The result of the study show that promotion positive and significant effect on customer satisfaction the quality of service has a positive effect and significant to customer satisfaction PT. Sayap Mas Utama.